Eco-Farming Revolution: Pemanfaatan Limbah Cair Tahu sebagai Pupuk Organik Cair Unggulan: Pengabdian - Almas Farah Dinna Dewi; Dimas Nur Slamet Aji Fernanda; Muhammad Zidny Irfan; Thalia Cendana Celloiva; Moh. Fadil Gezali; Moh. Dafa Rachmadani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Extension on the use of liquid organic fertilizer from tofu liquid waste was conducted in Sumberwaru Village. The extension aimed to increase understanding and practice of sustainable agriculture. Tofu liquid waste has potential as a source of organic fertilizer that is rich in nutrients, improves soil fertility, increases plant growth, and reduces dependence on chemical fertilizers. This tofu liquid waste extension teaches mosque youth in Sumberwaru Village about the production method of liquid organic fertilizer from tofu liquid waste through a 15 days fermentation process with the help of EM4 and application to plants. The application of this knowledge not only reduces environmental pollution but also increases crop yields by using environmentally friendly fertilizers. The results of the extension showed that the application of liquid organic fertilizer from tofu liquid waste can reduce the volume of waste disposed to the environment and produce something useful. This extension also succeeded in increasing the knowledge of mosque youth about waste management and the practice of making liquid organic fertilizer.